Implementation of Humanistic Learning Theory in Islamic Religious Education Learning at Madrasah Tsanawiyah in Palu City - Halik, Abdul; Fatmah (Yayasan Pendidikan Islam (YPI) AN NUR INSANI, 2025)
This study aims to analyze the implementation of humanistic learning theory in the teaching of Islamic Religious Education (PAI) at Madrasah Tsanawiyah (MTs) in Palu City. Humanistic learning theory emphasizes the holistic development of students' self-potential, which aligns with the goals of Islamic education. The research method used is descriptive qualitative, employing techniques such as observation, interviews, and documentation. The findings show that the application of humanistic learning theory in PAI instruction at MTs in Palu City has had a positive impact on students’ learning motivation, character development, and understanding of Islamic values. However, there are still some challenges in its implementation, such as limited facilities and infrastructure, as well as teachers’ understanding of the humanistic concept.